PREDIKSI MORFOLOGI JAMUR MENGGUNAKAN ALGORITMA C5.0 - Lita Karlitasari; I Wayan Sriyasa; Irfan Wahyudi; Heri Bambang Santosi (Universitas Teknokrat Indonesia, 2023)
Mushrooms are divided into two, namely edible mushrooms and poisonous mushrooms. to distinguish between types of mushrooms that can be consumed from those that are poisonous is a complicated matter because of the nearly identical forms of the various species of mushrooms. One way to identify mushrooms is by way of morphology later which will be able to know what class a fungus belongs to. The algorithm is used because it is faster, because it is multithreaded, but otherwise produces exactly the same classifiers. shows that the C5.0 algorithm has a very good accuracy value of 99-100% with a fairly good amount of power, using both split validation and cross-validation. And also almost all attributes have a significant relationship or influence, because they have an expected value of less than 5%. Using keywords related to the research topic is recommended.